Developing Strategies For Competitive Advantage : A Study On Ann Joo Resources Berhad - Hooi, Chet Kai (2010)
This paper seeks to develop strategies for Ann Joo Resources Berhad (AJR) in creating competitive advantages especially during this crucial time. This is achieved through a case study of AJR who is in Malaysian upstream steel businesses.